The Correlation Between the Criminal Sentence Period and the Intention of Prisoners to Stop Using Drugs in Class I Correctional Facility of Bandar Lampung - Aditia Arief Firmanto; Prida Harkina; Vira Sandayanti (Universitas Ahmad Dahlan, 2021)
Introduction to the Problem: The length of the criminal sencenting can create an intention in prisoners to stop using drugs. Psychologically, the intention is seen from how strong a person's desire to display behavior and how much effort is planned or will be made to display behavior.Objective: This study intends to determine the relationship between the length of the sentence and the intention to stop using drugs in Class I prisons of Bandar Lampung. The variables in this study were the length of the sentence and the intention to stop using drugs. The research samples in this study were the drug convicts in Class I Correctional Facility of Bandar Lampung,Methodology: Data collection method uses quantitative and combines with the qualitative method. The data analysis method of descriptive quantitative uses Linkert Scale approach accumulated with the Pearson Product Moment correlation technique by using the Statistical Packages for Social Sciences 20 application program. Data analysis method of qualitative descriptive uses empirical normative approach.Findings: The result in this study is that there is no relationship between the length of the sentence and the intention to stop using drugs in the Class I Correctional Facility in Bandar Lampung. Based on the correlation test results, the r value was -0.088 with significance = 0.381 where (p> 0.05). The data shows the relationship between the length of the sentence and the intention to stop using drugs in the Class I Correctional Facility in Bandar Lampung is not proven. It means that there are other aspects that more influencing the intention of drug use. Additionally, the effectiveness of imprisonment for drug users in the Class I prison in Bandar Lampung has not run optimally, namely supporting facilities and facilities such as overcapacity for prisoners and prisoners.Paper Type: Research Article